An experimental analysis of shell failure in breast implants. (August 2017) - Ramião, N.G.; Martins, P.S.; Barroso, M.L.; Santos, D.C.; Fernandes, A.A.
Abstract: Breast implant durability and the mechanisms of rupture are important topics in the medical community, for patients, manufactures and regulatory medical agencies. After concerns about the Poly Implant Prosthesis (PIP) implants, the need for understanding the adverse outcomes and the failure mode to improve the breast implants increased. The objective of this research is to analyze and describe the rupture characteristics of failed explanted PIP implants to study the modes and causes of rupture. Eleven explanted PIP implants were analyzed by visual inspection and scanning electron microscopy (SEM). To simulate hypothetical ruptures caused by cyclic mechanical stress (fatigue) in the implant shell, two control implants were submitted to fatigue tests, and analyzed with SEM. Small ruptures (either Hole or split) striations were found, which normally appear due to fatigue phenomena. Similar striations were also found in specimens (control) tested under laboratory controlled conditions. In the context of this work, the striations found in explants constitute a significant finding as they point to the occurrence of fatigue phenomena associated with mammary implants rupture. This research, also demonstrates that rupture surface analysis of explanted breast implants has the potential to become a useful indicator for assessing implant rupture mechanisms.